The state and problems of common black soils’ fertility in Poltava region - Dereza, V. (Scientific Progress & Innovations, 2023)
The natural quality and modern state of soils is the determining factor, which ensures the productivity and effectiveness of agricultural production. Crop yield capacity directly depends on soils’ fertility, which are the independent natural element and component of the eco-system. The purpose of the article is to study the current state of fertility of black soils’ fertility in Poltava region and to determine the factors that cause its deterioration. Soils are a complex system, in which substances and energy metabolism with the natural environment constantly takes place. Black soils occupying the two-third of the Central Ukraine’s territory are the most fertile soils. Common black soils are the most wide-spread and in Poltava region and they are located in the southern parts of Kobeliaky, Novi Sanzhary, Mashivka, and Karlivka districts. The fertility of these black soils is under the negative effect of intensive practices and technologies of agricultural production. It has been established that during the period of 2013–2020, humus content in these soils decreased by 5.5 %, which shows the insufficiency of receiving organic substances relative to their biological losses because of mineralization processes, erosion, etc. The unbalanced deficit farming system dominating in Poltava region results in transforming the richest soils in the world into the soils with the average fertility level (45–65 points), which have the dynamics to further degradation. Moreover, common black soils are characterized by the considerable level of pollution with heavy metals (iron, zinc, chrome, nickel – most of all, lead, copper – insufficiently). It has been determined that the black soils in Kobeliaky and Mashivka districts are the least polluted (the content of heavy metals in these soils makes 1–10 mg/kg), while the black soils in Novi Sanzhary and Karlivka districts are the most polluted (21–30 mg/kg). The revealed negative factors affecting common black soils’ fertility in Poltava region show that the existing approach to their use in agricultural production is inadmissible.